Analisis User Experience Aplikasi PeduliLindungi Pada Pusat Perbelanjaan di Kota Semarnag - Meita Maulani Savitri; Haikal Haikal; Eti Rimawati; Muhammad Iqbal (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2023)
The PeduliLindungi application is the result of the Ministry of Communication and Information Technology's collaboration with SOEs to stop the spread of COVID-19. This application will be combined with Satu Data Kesehatan for citizen health evaluation. The purpose of this research is to analyze the User Experience of the PeduliLindungi application in shopping centers in Semarang City. By using the User Experience Questionnaire (UEQ) approach to evaluate various characteristics of User Experience. User experience refers to individual perceptions and reactions resulting from the use of a product. The population of this study consisted of users of the PeduliLindungi application, and the sample used was in accordance with the established criteria with a total of 99 samples. This research took place for one month in March-April 2023 and using a cross sectional method. The data obtained was processed using the UEQ Data Analysis Tool. The results of this study found that the clarity aspect scored (1.62) with an average of Good category. The aspects of attractiveness, accuracy, stimulation, and novelty scored (1.08), (1.05), (0.91), and (0.57) respectively in the Below Average category. And the efficiency aspect scored (0.90) in the Above Average category. The findings of this study are anticipated to be taken into account when PeduliLindungi is improved in terms of aesthetics and usage.